Determinants of growth retardation in Southern Brazil - Denise Aerts; Maria de Lourdes Drachler; Elsa Regina Justo Giugliani
A cross-sectional population-based study of determinants of growth retardation in under-five children (3,389) in the city of Porto Alegre, Rio Grande do Sul, Brazil estimated odds ratios (OR) for stunting, defined as height-for-age < -2 z-scores of the NCHS standards. Hierarchical modeling based on a framework of the process of stunting was used. Stunting prevalence was 6.8%; the main determinants were per capita family income < 0.8 times the minimum wage (OR: 3.95; 95%CI: 2.10-7.42), maternal illiteracy (OR: 17.17; 95%CI: 4.43-66.54), living in a wooden or mixed-construction house (OR: 2.33; 95%CI: 1.35-4.01), inadequate housing (OR: 2.75; 95%CI: 1.70-4.43), maternal age at the child's birth < 20 years (OR: 1.73; 95%CI: 1.11-2.70), being an adopted child (OR: 3.28; 95%CI: 1.52-7.07), third-born child or greater (OR: 2.04; 95%CI: 1.15-3.62), birth interval < 24 months since previous child (OR: 1.69; 95%CI: 1.13-2.53), subsequent sibling (OR: 1.91; 95%CI: 1.16-3.13), multiple birth (OR: 2.40; 95%CI: 1.04-5.50), low birth weight (OR: 3.79; 95%CI: 2.38-6.02), and hospitalization in the first year of life (OR: 1,65; 95%CI: 1.01-2.68).The findings can be used by primary healthcare services to design specific interventions to prevent stunting.